Grantham Trades Council exhibition float, 1958 (London, 1958)
1958 1951-1960 "Grantham Trades Council exhibition float, 1958" [BW0122], 1958, Trades Union Congress In 1958, Grantham Trades Council organised a mobile recruitment and publicity exhibition, including an Amalgamated Engineering Union banner on this lorry provided by the Grantham Cooperative Society Coal Department.